Experimental study and numerical simulation on dynamic soil‐structure interaction under earthquake excitations. Issue 138 (November 2020) - Liu, Shutong; Li, Peizhen; Zhang, Wenyang; Lu, Zheng
Abstract: Soil-structure interaction (SSI) phenomena subjected to seismic loadings are investigated in this study. Firstly, shaking table tests on dynamic soil‐structure interaction subjected to seismic loadings are carried out, and SSI effects are analyzed through a comparative study between the soil-structure system and the rigid foundation condition. Then, a corresponding numerical model on the SSI tests is presented. In the finite element model, a bounding surface plasticity model and an equivalent linear method are separately used for simulating the nonlinear behavior of soil. It turns out that the calculated results by the bounding surface plasticity model agree much better with the experimental results. Finally, the effects of different soil types and structural properties on soil-structure interaction are discussed by numerical parametric study. The results show that SSI effects noticeably mitigate the dynamic response of structure, and the closer the frequency of superstructure to the soil frequency, the more obvious the effect of soil-structure interaction. With increased shear wave velocity of soil, the impact of soil-structure interaction weakens. It is important for studying the impact of SSI on structural responses and practical engineering design purposes. Highlights: Shaking table tests of a six-story steel frame model considering soil-structure interaction (SSI) are conducted. SSI effects are analyzed through comparative study between the soil-structure system and the rigid foundation condition. a three-dimensional finite element model on the shaking table tests is established and verified. The equivalent linear method and bounding surface plasticity model are used respectively for nonlinear behavior of soil. Extensive parametric studies with different nonlinear soil types and structural properties are considered.